mecA Gene Transferrability and Antibiogram of Zoonotic Staphylococcus intermedius from Animals, Staff, and the Environment in Animal Hospitals in Korea - Youn, J.H., Seoul National University, Seoul, Republic of Korea; Hwang, S.Y., Seoul National University, Seoul, Republic of Korea; Kim, S.H., Seoul National University, Seoul, Republic of Korea; Koo, H.C., Seoul National University, Seoul, Republic of Korea; Shin, S., Seoul National University, Seoul, Republic of Korea; Moon, B.Y., Seoul National University, Seoul, Republic of Korea; Lim, S.K., National Veterinary Research and Quarantine Service, MAF, Anyang, Republic of Korea; Park, Y.H., Seoul National University, Seoul, Republic of Korea (Journal of microbiology and biotechnology, 2010)
Staphylococcus intermedius is a common cause of otitis externa, pyoderma, and wound infections in companion animals. Although S. intermedius infections are rare in humans, it is zoonotic, with several case reports describing fatal human infections. Presently, we sought to isolate S. intermedius strains from various sources at animal hospitals nationwide in Korea, examine their antibiotic susceptibilities, and determine the possibility of horizontal transmission between animals and humans. Pulsed-field gel electrophoresis (PFGE) was used to compare the mecA gene in S. intermedius strains from humans, animals, and the environment in animal hospitals. A total of 119 S. intermedius strains were isolated from 529 samples. Using the disk diffusion method, over 90% of the isolates were found to be susceptible to cephalothin, amoxicillin-clavulanic acid, vancomycin, imipenem, nitroflurantoin, and amikacin, whereas 97.5% and 98.3% of the isolates were resistant to penicillin and ampicillin, respectively. Among the 39 S. intermedius strains harboring mecA, similar PFGE patterns were observed between seven isolates from an animal, two isolates from veterinary staff, and the environment in one animal hospital, and single isolates from an animal and a veterinarian at another hospital. This result suggests the possibility of horizontal transmission of S. intermedius containing mecA between humans, animals, and the environment in animal hospitals and also emphasizes on the importance of S. intermedius with mecA as a possible emerging threat to public health.